Inflammatory Markers as Prognostic Factors of Survival in Patients Affected by Hepatocellular Carcinoma Undergoing Transarterial Chemoembolization. (15th August 2017) - Rebonato, A.; Graziosi, L.; Maiettini, D.; Marino, E.; De Angelis, V.; Brunese, L.; Mosca, S.; Metro, G.; Rossi, M.; Orgera, G.; Scialpi, M.; Donini, A.
Abstract : Introduction . Transarterial chemoembolization (TACE) is a good choice for hepatocellular carcinoma (HCC) treatment when surgery and liver transplantation are not feasible. Few studies reported the value of prognostic factors influencing survival after chemoembolization. In this study, we evaluated whether preoperative inflammatory factors such as neutrophil to lymphocyte ratio and platelet to lymphocyte ratio affected our patient survival when affected by hepatocellular carcinoma. Methods . We retrospectively evaluated a total of 72 patients with hepatocellular carcinoma that underwent TACE. We enrolled patients with different etiopathogeneses of hepatitis and histologically proven HCC not suitable for surgery. The overall study population was dichotomized in two groups according to the median NLR value and was analyzed also according to other prognostic factors. Results . The global median overall survival (OS) was 28 months. The OS in patients with high NLR was statistically significantly shorter than that in patients with low NLR. The following pretreatment variables were significantly associated with the OS in univariate analyses: age, Child-Pugh score, BCLC stage, INR, and NLR. Pretreated high NLR was an independently unfavorable factor for OS. Conclusion . NLR could be considered a good prognostic factor of survival useful to stratify patients that could benefit from TACE treatment.